Model Transparansi Keuangan Digital Untuk Pencegahan Korupsi di Sekolah Menengah - Tinuk Dwi Cahyani; Fauziyah Fauziyah; Lutfi Ali Muharom; Sony Zakaria (University of Muhammadiyah Malang, 2026)
Corruption is a problem that can hamper the economy and undermine public trust in government. Low and weak transparency are often the main factors that open up opportunities for corruption. Preventing corruption requires a systematic approach, one of which is through the formulation of an efficiency and transparency model using information technology. This study aims to analyze the role of information technology systems in increasing efficiency and transparency to prevent corruption. The purpose of this study is to formulate an efficiency and transparency model using an electronic information system to prevent corruption. This study applies qualitative methods with a literature review and data collection through Focus Group Discussions (FGDs) with SMA Muhammadiyah 3 Jember. The components of the information technology system developed are dashboards containing data such as planning, realization, and budget distribution based on work units and programs. The novelty of this research in the development of a school financial transparency model in a digital system that cimbines stages of verification, realization, uploading evidence and monitoring. This study emphasizes that strengthening information technology systems requires data integration and human resource development. No matter how well a digital system is implemented, without ethics and a commitment to anti-corruption, technology can be manipulated. Therefore, with an integrated and open information system, disclosure of suspected corruption can be done quickly and efficiently.